(untitled) (GYMNASIUM, 2011)
The research objective is represented by the sportive training process for junior football players, based on shaping the tactical training at the level of the junior A players. The subject of the present research is that of shaping the tactical training of junior A players inside the Republican Championship. The purpose of the study: the experimental underlining of improving sportive training and differentiating the tactical training of players at the level of the junior national lots.